Human pancreatic tumour organoid‐derived factors enhance myogenic differentiation. Issue 2 (11th February 2022) - Vaes, Rianne D.W.; van Dijk, David P.J.; Farshadi, Elham Aïda; Olde Damink, Steven W.M.; Rensen, Sander S.; Langen, Ramon C.
Abstract: Background: Most patients with pancreatic cancer develop cachexia, which is characterized by progressive muscle loss. The mechanisms underlying muscle loss in cancer cachexia remain elusive. Pancreatic tumour organoids are 3D cell culture models that retain key characteristics of the parent tumour. We aimed to investigate the effect of pancreatic tumour organoid‐derived factors on processes that determine skeletal muscle mass, including the regulation of muscle protein turnover and myogenesis. Methods: Conditioned medium (CM) was collected from human pancreatic cancer cell lines (PK‐45H, PANC‐1, PK‐1, and KLM‐1), pancreatic tumour organoid cultures from a severely cachectic (PANCO‐9a) and a non‐cachectic patient (PANCO‐12a), and a normal pancreas organoid culture. Differentiating C2C12 myoblasts and mature C2C12 myotubes were exposed to CM for 24 h or maintained in control medium. In myotubes, NF‐kB activation was monitored using a NF‐κB luciferase reporter construct, and mRNA expression of E3‐ubiquitin ligases and REDD1 was analysed by RT‐qPCR. C2C12 myoblast proliferation and differentiation were monitored by live cell imaging and myogenic markers and myosin heavy chain (MyHC) isoforms were assessed by RT‐qPCR. Results: Whereas CM from PK‐1 and KLM‐1 cells significantly induced NF‐κB activation in C2C12 myotubes (PK‐1: 3.1‐fold, P < 0.001; KLM‐1: 2.1‐fold, P = 0.01), Atrogin‐1/MAFbx and MuRF1 mRNA were only minimally and inconsistently upregulated by the CM of pancreatic cancer cell lines. Similarly, E3‐ubiquitin ligases and REDD1 mRNA expression in myotubes were not altered by exposure to pancreatic tumour organoid CM. Compared with the control condition, CM from both PANCO‐9a and PANCO‐12a tumour organoids increased proliferation of myoblasts, which was accompanied by significant downregulation of the satellite cell marker paired‐box 7 ( PAX7 ) (PANCO‐9a: −2.1‐fold, P < 0.001; PANCO‐12a: −2.0‐fold, P < 0.001) and myogenic factor 5 ( MYF5) (PANCO‐9a: −2.1‐fold, P < 0.001; PANCO‐12a: −1.8‐fold, P < 0.001) after 48 h of differentiation. Live cell imaging revealed accelerated alignment and fusion of myoblasts exposed to CM from PANCO‐9a and PANCO‐12a, which was in line with significantly increased Myomaker mRNA expression levels (PANCO‐9a: 2.4‐fold, P = 0.001; PANCO‐12a: 2.2‐fold, P = 0.004). These morphological and transcriptional alterations were accompanied by increased expression of muscle differentiation markers such as MyHC‐IIB (PANCO‐9a: 2.5‐fold, P = 0.04; PANCO‐12a: 3.1‐fold, P = 0.006). Although the impact of organoid CM on myogenesis was not associated with the cachexia phenotype of the donor patients, it was specific for tumour organoids, as CM of control pancreas organoids did not modulate myogenic fusion. Conclusions: These data show that pancreatic tumour organoid‐derived factors alter the kinetics of myogenesis, which may eventually contribute to impaired muscle mass maintenance in cancer cachexia.